Peran Psikologi dalam Pemilihan Konten dan Proses Pembelajaran - Assyifa Handayani (Tarbiyah : Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This article analyzes the foundation of a curriculum based on developmental psychology and learning psychology and their respective implications. The method used in this article is literature review or library research. Where researchers collect data from various library sources, such as books, journals, scientific articles, research reports such as theses and dissertations, as well as other sources relevant to the research topic. Student have unique competencies in each phase of development psychology so that educators and curriculum developers can provide treatment that is appropriate to the developmental stage. Because psychology has implications for content and implementation, as well as learning evaluation. Meanwhile, Learning Psychology, which includes Behavioristics, Cognitive Psychology, Constructivism, Phenomenology and Humanism, has implications for determining learning methods by considering the characteristics of students, both in terms of motivation, interests, talents and learning styles that they have. So this article concludes that teachers' literacy willingness to explore the foundations of developmental psychology and learning psychology influences their ability to design and develop in-depth curriculum and meaningful learning.